Exploring Speaking Anxiety in English Language Learning: Causes and Coping Strategies among University Students - Endang Darsih; Vina Agustiana; Wulan Rahmatunisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Speaking anxiety in English as a Foreign Language (EFL) learning remains a challenge that affects students’ communicative performance, while integrated studies linking its causes and coping strategies are still limited. This study aims to analyze the determinants of speaking anxiety and evaluate the coping strategies employed by second-year university students. Using a qualitative case study design, six purposively selected participants were involved. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings indicate that speaking anxiety is influenced by fear of making mistakes, limited vocabulary, and insufficient preparation, which affect students’ confidence and fluency. To manage these challenges, participants employed strategies such as preparation, relaxation, positive thinking, peer support, and acceptance. The results highlight that while preparation is important, positive thinking plays a more dominant role in alleviating anxiety. The study implies the need to integrate affective strategies, particularly positive mindset development and emotion regulation, into instructional practices to foster supportive and low-anxiety learning environments.